PELATIHAN PENGGUNAAN APLIKASI QUIZLET UNTUK PEMBUATAN SOAL MATEMATIKA PADA MATERI GEOMETRI DI SMP - Alfi Yunita; Zulfitri Aima; Audra Pramitha Muslim (Unmuh Babel Press, 2021)
Based on the results of interviews at partner schools, namely SMPN 27 Padang, it can be seen that the learning process carried out by teachers during the COVID-19 Pandemic is a learning process using throught WhatsApp by giving assignments to students. Therefore, the proposer and partners work together in overcoming these problems through the Community Service (PKM) program. This PKM program aims to increase teachers' knowledge about the application of online learning models, so training on the use of the Quizlet Application for Making Mathematics Problems in Geometry Material been given. The method used in achieving these goals is a simulation method and practice using the Quizlet application. The result of this community service is to increase teacher knowledge in using the Quizlet application in the mathematics learning process.